Gupak Pulute Ora Mangan Nangkane PERAN PARA AGEN DAN HUBUNGAN KEKUASAAN KORBAN LUMPUR (LAPINDO) DI BESUKI TIMUR, JABON, SIDOARJO - , AZZAH NILAWATY; , Sir J. Nicolaas Waraouw ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis is about relations of power in the industry Lapindo mudflow disaster stage at the national level. More specifically in the context of power relations Lapindo mudflow victims in Besuki East with the actors (as an outside agency). The power relations embodied in a forms of resistance, negotiation and accommodation. Power relations that occur between the actors because there is interest among some parties need each other. The agent consists of mudflow victims (people of East Besuki), states, nongovernmental organizations (NGOs) and the media. During field observations, quite a lot of symptoms of the practice of negotiation and accommodation between the victims of the mud with the agents. The relationship can be seen when the actors intersect. In addition, the relationship of power occurs because the unilateral policy making mud victims to fight as a form of rejection policy. This research study aims to determine how the role of the state agencies, NGOs and the media to mudflow victims in Besuki East. In addition to tracing the power relations that occur between mudflow victims with the agents. Primary data through interview techniques ethnography, personal narrative, observation, participatory observation, life history and field notes. Secondary data using the method of literature, print media, electronic media and internet media. The results of this research indicate that the agents mutually 'scramble' influence in the field and collide Lapindo mudflow victims. Habitus and capital of each agent to be an important record for the people of East Besuki. Each agent taking advantage themselves according to their interests. In the end East Besuki public response to state policy and the role of other agencies are not always frontal. They also did the practice of negotiation and accommodation. East Besuki people use logical reasoning with them as state (governmentality).